ENGAGEMENT AND WORK ATTITUDE TOWARDS PERFORMANCE OF EMPLOYEES AT SERBA JADI CAMAT OFFICE, SERDANG BEDAGAI, NORTH SUMATRA - Syamsuri, Abd. Rasyid; Lingga, Linda Hartaulina; Suriandi; Yuliannisa, Layla; Putri, Laila Kurnia (Jurnal Bisnis Mahasiswa, 2022)
The purpose of this study is to analysis into the impact of job involvement and attitude on the performance of Serba Jadi Camat Office personnel in Serdang Bedagai Regency, North Sumatra, in both a partial and simultaneous manner. The participants in this study were 35 Serba Jadi Camat Office personnel from the Serdang Bedagai Regency in North Sumatra. Observation and questionnaires were used to obtain data. Job involvement had a positive and significant effect on the performance of Serba Jadi Sub-District Office personnel in Serdang Bedagai Regency, North Sumatra, according to the findings. Serba Jadi Sub-District Office staff in Serdang Bedagai Regency, North Sumatra, have a favorable and significant effect on their performance. Employees of the Serba Jadi Sub-District Office in the Serdang Bedagai Regency, North Sumatra, have a positive and significant effect on their performance. Work involvement and work attitude account for 54.0 percent of employee performance, with the remaining 46.0 percent explained by characteristics not investigated in this study.